From Coal to Wind: How the Danish Energy Policy changed in 1990. Issue 4 (8th August 2019) - Rüdiger, Mogens
Abstract : In March 1987, the Brundtland Report –Our Common Future – was published by the UN's World Commission on Environment and Development. The recommendations of the report contributed worldwide to raising awareness of climate change. In particular, the energy sector became the object of anxiety, as production and the use of energy were pinpointed as some of the 'crooks' emitting most greenhouse gasses. Shortly after the publication of the report, the Danish government revised its energy planning and opened up for a radical change of the energy sector. This article delves into this crucial change and, in doing so, suggests a historical answer to the question of why Denmark became one of the leading nations in transforming the energy sector from a power supply based on fossil fuels to a power generation system using a high percentage of renewables.